Kai or Kiwi? Māori and 'Kiwi' cookbooks, and the struggle for the field of New Zealand cuisine. (June 2013) - Morris, Carolyn
Māori food has minimal presence in the New Zealand public culinascape, though that presence is growing. There are a few restaurants, a range of condiments made Māori by particular culinary herbs, and a number of Māori food festivals. Moreover, since 2008 four Māori cookbooks have been published and three of them were distributed through mainstream book shops. The question this article addresses is the significance of the almost-simultaneous publication of these cookbooks. It is suggested that the cookbooks are part of a tale of struggle between Māori and Pākehā for their relative places in the nation; of Māori efforts to improve their position, and Pākehā efforts to maintain their position. This strategy seems to be leading to a restructuring of the field of cuisine through a reordering of the values of the capitals that constitute the field.